2018
DOI: 10.17146/jsmi.2016.18.1.4186
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Suhu Kalsinasi Pada Proses Dekomposisi Dolomit

Abstract: Proses dekomposisi dolomit menjadi MgO dan CaO merupakan proses penting mengingat kedua oksida tersebut banyak digunakan dalam berbagai aplikasi. Untuk melihat pengaruh suhu proses kalsinasi terhadap dekomposisi dolomit menjadi MgO dan CaO, maka dilakukan kalsinasi. Proses kalsinasi menggunakan tungku Muffle furnace dengan suhu sebesar 500 o C, 600 o C, 700 o C, 800 dan 900 o C. Sebanyak kurang lebih 100 gram/sampel dolomit dimasukkan dalam tungku dan dipanaskan dengan laju pemanasan 10 o C/menit pada berbagai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…The calcination of the sample done by using a furnace with a temperature of 800 ºC for 3 hours to remove carbonate that can inhibit crystal formation and eliminate all organic elements contained in the bones of mackerel. (Royani et al, 2016) mentioned the decomposition of CaCO 3 into CaO ideally occurs at a temperature of 800 ºC. At this stage, there was a decomposition reaction of calcium carbonate (CaCO 3 ) to calcium oxide (CaO) Reactions that occurred according to eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calcination of the sample done by using a furnace with a temperature of 800 ºC for 3 hours to remove carbonate that can inhibit crystal formation and eliminate all organic elements contained in the bones of mackerel. (Royani et al, 2016) mentioned the decomposition of CaCO 3 into CaO ideally occurs at a temperature of 800 ºC. At this stage, there was a decomposition reaction of calcium carbonate (CaCO 3 ) to calcium oxide (CaO) Reactions that occurred according to eq.…”
Section: Resultsmentioning
confidence: 99%
“…In this study set, the basic condition of pH 12 was controlled using NaOH 1 M. Samples was calcined at a temperature of 900 ºC for 5 hours aimed to increasing the degree of crystallization (Haris et al, 2016), eliminate carbonate which can maximized the formation process of hydroxyapatite (HAp) (Ningsih et al, 2014). Heating at 900 ºC indicated that the samples used from the bones of the mackerel have a good thermal stability characterized by the formation of hydroxyapatite (HAp) (Royani et al, 2016). The reaction was in eq.…”
Section: Hydroxyapatite Synthesis (Hap)mentioning
confidence: 99%
“…The yield decreasing showed that the cockle shells had decomposed during the heating process. The decomposed phase was calculated from the change in weight of the sample to the initial weight of sample [17]. It could be seen that the maximum was achieved at a temperature of 1000 ºC, which was 55.13%.…”
Section: Figure 1 Cao Powder Produced By Calcination Cockle Shells Fr...mentioning
confidence: 99%
“…Tahap pertama terjadi pada temperatur 700˚C, sedangkan langkah kedua terjadi pada temperatur 740˚C [1]. Kalsinasi dolomit dipengaruhi oleh beberapa parameter seperti: komposisi dolomit, densitas dan ukuran partikel, temperatur kalsinasi, dan atmosfer dalam tungku [1,2,3,4,5].…”
Section: Pendahuluanunclassified